Estimation of Stature from Hand Measurements. A Population based Study - Fouzia Hameed; Vina Vaswani; Viswakanth B (Indian Journal of Forensic Medicine & Toxicology, 2021)
A prospective study was carried out in the department of Forensic Medicine and Toxicology, KanachurInstitute of Medical sciences, Mangaluru in 2016. The aim of the study was to evaluate the stature fromhand length and hand breadth in Dakshina Kannada population. Materials and method: The study groupcomprised of 100 individuals of ages ranging from 22-45 years of both males and females (50 males and 50females) residing in Dakshina Kannada. Individuals were selected randomly who attended Kanachur hospitalin the age group of 22-45 years of both males and females. Written informed consent was taken from eachindividual. Ethical clearance was obtained from Yenepoya University to carry out the study. Materials usedwere stadiometer, digital caliper. Results: The linear regression analysis and multiple regression equationwere obtained for both males and females. Conclusion: Linear regression equation is useful in estimatingstature than multiple regressions. To denote a population it is always better to do on a larger sample size toget accuracy of the results.